Enhanced thermoelectric properties exhibited by unreduced freestanding graphene oxide/carbon nanotube membranes. Issue 17 (17th June 2021) - Islam, Md. Saidul; Ohmagari, Hitomi; Rahman, Mohammad Atiqur; Shudo, Yuta; Fukuda, Masahiro; Yagyu, Junya; Sekine, Yoshihiro; Lindoy, Leonard F.; Hayami, Shinya
Abstract : The considerable thermoelectric power factor of 5.33 × 10 −2 μW mK −2 observed for unreduced GO/CNT (1 : 2 ratio) implies the suitability of unreduced GO/CNT as a flexible thermoelectric material. Abstract : Herein we determine the Seebeck coefficients, electric conductivities, and thermoelectric power factors of a range of unreduced graphene oxide (GO)/single-wall carbon nanotube (CNT) membranes incorporating different GO/CNT ratios as well as of a series of reduced graphene oxide (rGO) membranes for which reduction had occurred at different temperatures. The considerable thermoelectric power factor of 5.33 × 10 −2 μW mK −2 generated from unreduced GO/CNT (1 : 2 ratio) is in agreement with its suitability for application as a flexible thermoelectric material. Moreover, compared to the conventional architectures of traditional thermoelectric materials, the inherent flexibility of GO-based thermoelectric materials opens the door to improved performance and efficiency, with lightweight, scalable, stretchable, and/or wearable materials being the outcome.